High-throughput screening approach to evaluate the adhesive properties of bacteria to milk biomolecules. (November 2018) - Gomand, F.; Borges, F.; Salim, D.; Burgain, J.; Guerin, J.; Gaiani, C.
Abstract: Adhesive interactions between bacteria and food have been increasingly studied in the last decades for probiotic bacteria especially in order to improve their protection and to help with biopreservation. The new approach described here has been designed to screen quickly a hundred of strains for their affinity differences for a given range of biomolecules. This method involves three steps: the biomolecules of interest are immobilized on microplates; the strains are then incubated on these microplates and non-adherent strains are removed by successive washes. Culture medium is then added and bacterial growth monitored through optical density measurements. The correlation between the time at which bacterial growth starts on the immobilized biomolecules and bacterial affinity for these biomolecules was first established. The method was then validated using the model strain Lactobacillus rhamnosus GG and three mutant strains lacking surface components involved in adhesion. The affinity of these strains was estimated for six dairy biomolecules. The method demonstrated that bacterial affinity can highly vary between different milk biomolecules. Affinity differences were mainly due to the presence or absence of bacterial surface biomolecules such as pili and exopolysaccharides. These findings may help with the understanding of the behavior of bacteria when incorporated into dairy foods. Graphical abstract: Image 1 Highlights: A high-throughput screening method for bacteria-biomolecule adhesion was developed. Levels of adhesion are compared using bacterial growth-starting times. Only bacterial growth conditions need to be known in order to implement this method. A maximum of 96 different strains can be screened at the same time. This method was validated on strains which feature well-known adhesive properties.